The study of retail image on La Mardia Bakery, Ocean Supermarket (Melaka City) as perceived by its customer / Andy Shahril Mohd Ariff - Andy Shahril, Mohd Ariff (1999)
Image is a picture formed in the mind of how a retailer perceive by its customer. The study of retail image overall is about perception held in shopper's mind determined by the ftmctional attributes and psychological attribute of the store. This study is concentrated on the retail image of La Mardia Bakery and how their customers evaluate mentally based on relevant store attributes, store environment and customer services provided by the store. La Mardia as the only Bumiputera bakery in Melaka city and only been three years in the market shares make it relevant for the researcher to know the perception of people toward La Mardia Bakery. Many references were made through next, journal, article and Internet, to know the previous finding of the study of retail image. The objective of the study is to know the main attributes of La Marida Bakery based on the functional psychological characteristic of the store. The second objective will be concentrated of the store environment impact toward the customer. Lastly the study want to determine the service that satisfied the present customer in La Mardia Bakery. The finding of the study was made based on the questionnaires result that have been distributed to 100 of La Marida bakery customers. The finding and analysis show that majorities of the respondent notice that staff appearance, merchandise, price, color, lightning and odor are the attributes of La Mardia Bakery. Majority of the respondent also agrees that store environment effect their emotional felling to spend at La Mardia bakery. Finally, the result show that customer service provided at La Mardia satisfy its customers. Recommendation was made at the end of this project paper after taking consideration the feedback from the customers. Hopefiilly all the recommendation would look through its positive aspect and not just a criticism to the company. Finally, overall conclusion was made according to the finding and objective of the study